Hyperglycemia causes cellular senescence via a SGLT2- and p21-dependent pathway in proximal tubules in the early stage of diabetic nephropathy - Kitada, Kento (2014)
AIMS: Kidney cells in patients with diabetic nephropathy are reported to be senescent. However, the mechanisms that regulate cellular senescence in the diabetic kidney are still unknown. In the present study, we evaluated the contribution of high glucose to renal cell senescence in streptozotocin (STZ)-induced diabetic mice. METHODS: Non-diabetic and streptozotocin (STZ, 10 mg kg(–1) day(–1) for 7 days, i.p.)-induced type 1 diabetic C57BL/6 J mice and cultured human proximal tubular cells were used in this study. RESULTS: Hyperglycemia dramatically increased the renal expression of p21 but not other CDK inhibitors such as p16 and p27 at 4 weeks after STZ injection. These changes were accompanied by an increase in senescence-associated β-galactosidase staining in tubular epithelial cells. Administration of insulin at doses that maintained normoglycemia or mild hypoglycemia suppressed the changes induced by STZ. Insulin did not affect the senescent markers in non-diabetic mice. Exposure of cultured human proximal tubular cells to 25 mmol/L, but not 8 mmol/L, glucose medium increased the expression of senescence markers, which was suppressed by knock-down of p21 or sodium glucose cotransporter (SGLT) 2. CONCLUSIONS: These results suggest that hyperglycemia causes tubular senescence via a SGLT2- and p21-dependent pathway in the type 1 diabetic kidney.